Functional characterization of podia formation in normal and malignant hematopoietic cells - Frühauf, Stefan; Srbic, Kornelija; Seggewiß-Bernhardt, Ruth; Topaly, Julian; Ho, Anthony Dick (Journal of leukocyte biology, 2002)
Hematopoietic cells extend multiple podia of yet unknown function. Our morphological studies using scanning electron microscopy and functional studies using time-lapse video microscopy suggest that podia formed by CD34+ hematopoietic stem cells (HSC) on the bone marrow stroma component fibronectin are characteristic of lamellipodia at the leading edge and uropodia at the trailing edge, cytoskeletal structures that have previously been shown to be responsible for cell locomotion of lymphocytes. In the leukemic cells studied here, stroma-derived factor-1α (SDF-1α) led to a significant eightfold increase in transmigration (BCR-ABL-positive BV173 leukemia cell line;P<0.05) and podia formation in all BCR-ABL-positive leukemic cell lines studied (BV173, K562, 32Dp210) and in two of three BCR-ABL-negative lines (HL60, 32D, not KG1a). We could show that SDF-1α exposure led to a down-regulation of the gene expression of the chemokine receptors CCR4, CXCR4, and CXCR5, which are associated with cell motility and podia formation, indicating a negative feedback control. In BCR-ABL-positive leukemic cells, the effects of SDF-1α on podia formation and cell migration were independent of BCR-ABL-tyrosine kinase activity. Our data are compatible with the hypothesis that formation of specific podia by hematopoietic cells is associated with egression of these cells from the bone marrow.
Gesehen am 21.01.2022
Die angegebene DOI funktioniert nicht. Stand: 21.01.2022